The occurrence and development of induced pluripotent stem cells - Chen, Yi; Li, Meng; Wu, Yanqing (Frontiers in Genetics, 2024)
The ectopic expression of four transcription factors, Oct3/4, Sox2, Klf4, and c-Myc (OSKM), known as "Yamanaka factors", can reprogram or stimulate the production of induced pluripotent stem cells (iPSCs). Although OSKM is still the gold standard, there are multiple ways to reprogram cells into iPSCs. In recent years, significant progress has been made in improving the efficiency of this technology. Ten years after the first report was published, human pluripotent stem cells have gradually been applied in clinical settings, including disease modeling, cell therapy, new drug development, and cell derivation. Here, we provide a review of the discovery of iPSCs and their applications in disease and development.